Towards sustainable shrimp culture in Thailand and the region. - Smith, Paul T., editor (Canberra, Australia ACIAR, 1999)
ACIAR Proceedings no. 90
Keywords: Thailand; Giant tiger shrimp culture--Thailand--Congresses.; PENAEUS MONODON; Giant tiger shrimp; Shrimps